The Principal's Strategy in Encouraging the Use of Educational Game-Based Learning Media - Pamilih Haryanti; Welius Purbonuswanto; Rejokirono Rejokirono (Journal of Creative Power and Ambition (JCPA), 2026)
The rapid advancement of information and communication technology has significantly transformed educational practices worldwide. This study aims to analyze the principal’s strategy in encouraging the use of Educational Game-Based Learning (EGBL) media at SD Negeri 2 Purwojiwo. The research employed a qualitative case study approach involving the principal and teachers as participants. Data were collected through interviews, classroom observations, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the principal implements several strategies, including instructional leadership, teacher professional development, motivational support, collaborative learning culture, and provision of learning facilities to promote the integration of EGBL in classroom instruction. These strategies help teachers gradually adopt and apply educational game-based learning to create more engaging and student-centered learning environments. However, the implementation also faces several challenges, such as varying levels of teacher digital competence, resistance to change, limited time, and insufficient technological infrastructure. Despite these obstacles, strong leadership and teacher collaboration serve as key supporting factors in the successful integration of EGBL. The study concludes that the principal’s leadership plays a crucial role in fostering innovation in teaching practices and enhancing the quality of learning through educational game-based learning media at the elementary school level.